A study on factor which give impact toward employee’s job satisfaction at Majlis Perbandaran Hang Tuah Jaya (MPHTJ), Jalan Tun Razak, Ayer Keroh, Melaka / Mohd Firus Hafizi Ismail - Ismail, Mohd Firus Hafizi (Faculty of Business and Management, 2012)
Job satisfaction can be as an important as indicator of how employees feel about their jobs and a predictor of work behaviors. Job satisfaction also plays an important role in defining employee’s efficiency and performance. Low job satisfaction will lead to the low morale and employees will concentrate more on negative aspect for example they will fell depresses, stress and absenteeism. Thus, this study aims to see factors which give impact toward employee’s job satisfaction. So which is motivation, work condition and pay will satisfy them. This study has been conducted within MPHTJ and it involved 152 respondents in different department. Pearson correlation coefficient is used to determine the strength of relationship between dependent variable and independent variable in the chapter four This researcher getting data for this research paper through questionnaires. Recommendation for future research are also have been discussed.